REKONSTRUKSI SUBJECTUM LITIS: REFLEKSI PEMBUBARAN PARTAI POLITIK SECARA KONSTITUSIONAL - Disantara, Fradhana Putra; Larasati, Niken; Wildani, Sahril; Hamid, Abdul; Valentino, Widhi (PMIH Untag Semarang, 2022)
Human rights as citizens must be respected and guaranteed, one of which is political rights. The guarantee of human rights must be able to provide moral strength that is able to protect and guarantee human dignity based on the law, not on the basis of circumstances, wills, or certain political perspectives. Citizens' political rights are the right to take part in government and vote regularly on democratic mechanisms in a country, whether through election, regional head elections, or other elections. The political right is related to the right of citizens to play a role in efforts to make future arrangements for a state institution. At the moment the request for dissolution of political parties can only be done by the government. The dissolution of political parties in Indonesia is carried out by the Constitutional Court as one of the institutions of judicial power. The political rights of citizens should be made a priority in the dissolution mechanism of political parties. This research is a normative juridical study which outlines a comparison of the dissolution of political parties between Indonesia and Germany and Slovenia. In addition, the mechanism for future improvement is the dissolution of political parties to better guarantee the political rights of citizens.